The SUMMIT Study: Utilising a written 'Next Steps' information booklet to prepare participants for potential lung cancer screening results and follow-up. (February 2023) - Bhamani, Amyn; Horst, Carolyn; Bojang, Fanta; Quaife, Samantha L; Dickson, Jennifer L; Tisi, Sophie; Hall, Helen; Verghese, Priyam; Creamer, Andrew; Prendecki, Ruth; McCabe, John; Gyertson, Kylie; et al.
Highlights: The majority of participants remembered receiving the booklet. Most participants found the booklet quite or very useful. Most participants reported that the booklet contained the right amount of information. Participants who remembered receiving the booklet were more likely to be satisfied with the process of results communication by letter. Abstract: Objectives: Low-Dose Computed Tomography (LDCT) screening for lung cancer can result in several potential outcomes of varying significance. Communication methods used in Lung Cancer Screening (LCS) programmes must, therefore, ensure that participants are prepared for the range of possible results and follow-up. Here, we assess perceptions of a written preparatory information booklet provided to participants in a large LCS cohort designed to convey this information. Materials and Methods: All participants in the SUMMIT Study (NCT03934866) were provided with a results preparation information booklet, entitled 'The SUMMIT Study: Next Steps' at their baseline appointment which outlined potential results, their significance, and timelines for follow up. Results from the LDCT scan and Lung Health Check were subsequently sent by letter. Perceptions of this booklet were assessed among participants with indeterminate pulmonary findings when they attended a face-to-face appointment immediately before their three-month interval scan. Specifically, questions assessed the perceived usefulness of the booklet and the amount of information contained in it. Results: 70.1% (n = 1, 412/2, 014) participants remembered receiving the booklet at their appointment. Of these participants, 72.0% (n = 1, 017/1, 412) found it quite or very useful and 68.0% (n = 960/1, 412) reported that it contained the right amount of information. Older participants, those from the least deprived socioeconomic quintile and those of Black ethnicity were less likely to report finding the booklet either quite or very useful, or that it contained the right amount of information. Participants who remembered receiving the booklet were more likely to be satisfied with the process of results communication by letter. Conclusion: Providing written information that prepares participants for possible LDCT results and their significance appears to be a useful resource and a helpful adjunct to a written method of results communication for large scale LCS programmes.